Global Experiences of State Regulation of Foreign Economic Activity - Boltayeva Sh. B.; Axmedova F. H. (Research Parks Publishers, 2021)
This article discusses the importance of foreign economic relations for the state economy, ways to create and develop activities. Information is provided on whether foreign economic relations should be regulated by the state, in what ways, and the experience of countries around the world in this area. It is obvious that there are opportunities and normative documents created in our country, but it is not enough, because there is a lot of work to be done to further develop the economy and ensure transparency.